Local flexibility market - Peter C. Cramton (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2022)
A local flexibility market is presented that addresses intrazonal congestion in a zonal electricity market. The market lets system operators access flexibility at multiple voltage levels to satisfy transmission constraints. Market participants offer local flexibility intraday in a continuous trading process. This supply is matched with demand from system operators. The market-based redispatch is transparent and technology neutral. Inc-dec gaming is mitigated with features to detect and sanction the behavior. Cost-based redispatch from conventional generation serves as a backstop if additional flexibility is required close to real time. This further mitigates inc-dec gaming by disciplining behavior in the spot market. An advantage of the approach in Europe is that it represents a modest change from the current market and therefore can be implemented sooner and with less risk.
Keywords: 330; local flexibility; congestion pricing; market design; electricity markets; electricity regulation